SP11.8 Postoperative outcomes are significantly worse among patients undergoing repair of ruptured versus unruptured iliac artery aneurysms – a 10-year longitudinal cohort study. (9th August 2022) - Laloo, Ryan; Aimar, Kelsey; Khanom, Johura; Bailey, Marc; Scott, Julian
Abstract: Aim: The European Society for Vascular Surgery defines iliac artery aneurysms (IAA) as beyond 1.5 times its normal diameter. Common iliac arteries (CIA) beyond 1.8cm in men and 1.5cm in women are considered aneurysmal. This study assessed outcomes following IAA rupture as their natural history is poorly understood with treatment recommendations based on low-level evidence. Method: Patients with IAAs at a single vascular centre between 1 st January 2010 and 31 st August 2021 were identified from a prospectively collected departmental database and Caldicott-approved data collection performed. The primary outcomes included aneurysm rupture, rupture diameter, post-operative complications, 30-day, 1-year and 5-year mortality rates. Statistical analysis with SPSS® was performed using chi-squared tests. Results: Of the 203 patients included, 90.6% were men and median(IQR) age at detection was 77 (71–83). Co-morbidities included hypertension (54.2%), hyperlipidaemia (42.9%) and ischaemic heart disease (35.5%). IAA were in the CIA (85.2%), IIA (21.7%) and EIA (2.0%), mostly asymptomatic (78.8%). Overall IAA rupture rate was 7.9% with CIA (81.2%) and EIA (18.8%). Mean (SD) diameters at rupture were 4.6 (2.4)cm for CIA and 4.6 (3.0)cm for IIA. Post-operative major adverse cardiovascular events (MACE) more frequently occurred following repair of ruptured compared to unruptured IAA (33.3% vs 3.5%, p=.011). Mortality at 30-days, 1-year and 5-years postoperatively were higher following repair of ruptured vs unruptured aneurysms (88.9%, 88.9%, 100% vs 1.2%, 10.6%, 36.1% respectively). Conclusion: Early detection and elective treatment of IAA aneurysms before they approach 4.6cm may reduce rupture risk, morbidity and mortality associated with emergency repair following rupture.